2020
DOI: 10.1016/j.indcrop.2020.112325
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic composition and biological activities of the in vitro cultured endangered Eryngium viviparum J. Gay

Abstract: Eryngium viviparum is an endangered species that requires management efforts based on complementary ex situ conservation strategies, such as in vitro culture. This study was carried out to evaluate the phenolic composition and the antioxidant, cytotoxic, and antimicrobial properties of E. viviparum aerial and root parts obtained by this micropropagation technique. The HPLC-DAD-ESI/MS n analysis showed that phenolic compounds were more abundant in the root (102 ± 4 mg g −1 extract) than in the aerial part (40.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 47 publications
(59 reference statements)
0
10
0
Order By: Relevance
“…Therefore, it appears that the antioxidant capacity of the plant extracts is possibly related to the phenolic composition, as shown in Section 3.1.3 . It is important to note that Trolox is a pure compound, while plant extracts are a mixture of compounds, with or without bioactive properties, which could explain the lowest antioxidant activity of the extracts when compared to Trolox [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it appears that the antioxidant capacity of the plant extracts is possibly related to the phenolic composition, as shown in Section 3.1.3 . It is important to note that Trolox is a pure compound, while plant extracts are a mixture of compounds, with or without bioactive properties, which could explain the lowest antioxidant activity of the extracts when compared to Trolox [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Rosmarinic acid (4) was identified by comparing it with a commercial standard and it was noted as the most abundant in the extract. This important antioxidant has also been identified as the most abundant compound in a hydroalcoholic extract of E. viviparum [32] and the second one in an aqueous extract of E. cymosum [33]. On the other hand, flavonol glycosides have been isolated and identified in several species of Eryngium [31], while isoflavones are less common.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, flavonol glycosides have been isolated and identified in several species of Eryngium [31], while isoflavones are less common. Ayuso et al reported, in 2020, the presence of three tectorigenin glycosides for the first time in the genus [32]. However, more chemical analysis is needed to identify this kind of flavonoids in E. longifolium.…”
Section: Discussionmentioning
confidence: 99%
“…Due to bioactive compounds, several Eryngium spp. have been used to treat human physiological disorders [9,10,11]. Although reports on pharmaceutical applications of E. foetidum are available, phytochemical investigation of leaves and the branches of E. foetidum, in particular, are scanty [12,13,14].…”
Section: Introductionmentioning
confidence: 99%